El taller : supervivencias y anacronismos - Miglioli, Viviana (2022)
Today, design studios are the core of the curriculum in the different schools of architecture. In these design studios, where project is taught, in discourses, practices, ways to relate and to live spaces, of teachers and students, survivals emerge, anachronisms corresponding to configurations of other times, which can be traced from a genealogy of the history of the design studio. Such survivals occur equally in design studios with different disciplinary paradigms, regardless of their institutional, contextual, or geographical adscriptions. \nThe surviving and anachronistic is not only detected as a discursive emergency, but, as these are practices, modes of relationship and ways of living, they can also be noted in the territory of what is visible. Through the construction of a theoretical methodological system, a work was carried out on the material recovered from the fieldwork developed in three Latin American architecture teaching institutions, and a fourth European, as well as on the images taken, and the data obtained from the study of documentary and iconographic archives. That theoretical-methodological system is composed of two resources: the consideration of the design studio as a foucauldian device -as a network linking heterogeneous elements to sustain a certain configuration of power-knowledge at a certain historical moment- and the realization of a warburgian atlas of the design studio- through the operation of montage of images from the past and present of the design studio, colliding temporalities, and senses. \nThe different regularities found through this work, illuminate survivals and anachronisms that need to be addressed, since they are usually not present in studies that deal with the current conditions of architecture training, and which need to be revealed, as a starting point to open new courses in the future of design studios and disciplinary education.